Moving forward to the future of healthcare - Jason Wolf (The Beryl Institute, 2020)
To say this moment in our shared global history feels shaky or uncertain for so many is not a statement of despair. Rather, it is acknowledging a reality through which we can best act and hopefully step through. As of the time this editorial will publish, well over 50 million cases of COVID-19 will have been reported. This is a reality all of humanity is sharing together; it is a challenge that healthcare is being called on to tackle. The work of people around the world to care for the sick, to find the right treatments and vaccines and the efforts of so many of our global citizens trying to do what they can to care for their families, friends and communities by doing the basics - wearing a face covering, maintaining physical distance, limiting the size of gatherings and more - is heroic. More so, I suggest it is human. Over the seven years of publishing PXJ, never could we have dreamt of this moment; but in many ways, we were always preparing for it. For in bringing together the diverse voices of our world, in weaving together ideas, stories and evidence we knew and now espouse, we are ready to support one another. We are truly stronger together. There is a time of work ahead as well as a time for healing, for working tirelessly to close gaps, to lower the temperature of rhetoric, for conversations on common ground and finding a path forward. Through your work in reading, contributing and engaging, we each can and will do our part. There are great possibilities ahead as we seek "a light of meaning," and those possibilities must forever guide us. Experience Framework This article is associated with the Culture & Leadership lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Culture%20%26%20Leadership%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens